1980
DOI: 10.1111/j.1365-2141.1980.tb08720.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Fibrinogen–Fibrin Related Antigen from Human Plasma by Immunoaffinity Chromatography: its Characterization in Normal Subjects and in Defibrinating Patients with Abruptio Placentae and Disseminated Cancer

Abstract: Highly purified fibrinogen-fibrin related antigen (FR-antigen) was isolated with good recovery from 1.0--2.0 ml of human plasma, by immuno-affinity chromatography with antibody specific for fibrinogen and fibrin, and plasmin degradation products X, Y, D and D-D dimer. In FR-antigen from defibrinating patients there was evidence for thrombin activity alone (mainly disseminated cancer) or both plasmin and thrombin (mainly abruptio placentae). Thus, the molar ratio of N-terminal Gly-Tyr in the FR-antigen of 18 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Indeed, there is abundant evidence that many tumor cells activate the coagulation system with generation of thrombin (37). Low-grade intravascular coagulation as diagnosed by increased fibrinogen turnover (38) increased plasma levels of fibrinogen/fibrin-related antigen (38) and increased plasma levels of fibrinopeptide A has been observed in most patients with solid tumors (39)(40)(41). One study noted elevated fibrinopeptide-A levels in 60% of patients at time of presentation with increasing levels noted with progression of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is abundant evidence that many tumor cells activate the coagulation system with generation of thrombin (37). Low-grade intravascular coagulation as diagnosed by increased fibrinogen turnover (38) increased plasma levels of fibrinogen/fibrin-related antigen (38) and increased plasma levels of fibrinopeptide A has been observed in most patients with solid tumors (39)(40)(41). One study noted elevated fibrinopeptide-A levels in 60% of patients at time of presentation with increasing levels noted with progression of disease.…”
Section: Discussionmentioning
confidence: 99%
“…50 Up-regulation of both VEGF and Ang-2 by thrombin indicates that angiogenesis might be facilitated by thrombosis. Thus, the well-described association of thrombosis with cancer [16][17][18][19][20] may be contributing to tumorigenesis by the initiation of thrombin-stimulated angiogenesis, which could explain, at least in part, the enhancement of experimental tumorigenesis by thrombin. [21][22][23][24][25] BLOOD, 1 MARCH 2002 ⅐ VOLUME 99, NUMBER 5 For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…16 Many studies have described a systemic activation of the blood coagulation cascade in patients with cancer. [17][18][19][20] Recent studies have shown that thrombin-treated tumor cells have an increased ability to adhere to von Willebrand factor, fibronectin, platelets, and endothelial cells and form pulmonary metastases in syngeneic mice. [21][22][23][24][25] However, the data do not define the mechanism by which thrombin promotes tumor progression and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…35 The binding of thrombin36,37 and factor X11I38 to fibrin may explain the increase in thrombin-catalyzed factor XIIIa by fibrin polymers in plasma.10 Prior studies provided indirect evidence for circulating crosslinked fibrin polymers by identifying y chain dimers in extracts of plasma obtained from patients with thrombotic disease. [15][16][17][18][19]39 Using an electrophoretic technique, we have shown directly a low concentration of crosslinked fibrin dimer in normal plasma and a significant elevation in patients with acute myocardial infarction. 7 Tissue plasminogen activator has a high affinity for fibrin29,30 and preferentially activates fibrinbound plasminogen,4041 which are properties that localize physiologic fibrinolysis and that also form the theoretical basis for the relative fibrin selectivity of t-PA as a therapeutic agent.…”
Section: Discussionmentioning
confidence: 99%